Conservative Management of Ectopic Pregnancy: A Population Based Study in Saudi Arabia (Journal of Fatima Jinnah Medical University, 2019)
Background: Ectopic pregnancy occurs in 1-2% of all pregnancies and remains a significant cause of first-trimester pregnancy-related mortality, accounting for 10-15% of such deaths worldwide. Traditionally managed through surgical interventions, recent advancements in diagnostic technologies, including transvaginal ultrasonography and serial serum β-hCG measurements, have facilitated the development of conservative management strategies. These approaches, particularly medical management with methotrexate, offer a promising alternative to surgery by preserving fertility and providing effective treatment in carefully selected patients.Patients and Methods: This prospective observational study was conducted at Gurrayat General Hospital over 2 years to evaluate the outcomes of conservative medical management for ectopic pregnancy using methotrexate. Patients received either a single-dose or multi-dose methotrexate regimen, and outcomes were assessed based on β-hCG levels, resolution time, and the need for surgical intervention.Results: Out of 50 patients with ectopic pregnancy, 90% achieved successful resolution with methotrexate therapy. 64% received a single-dose regimen, with 81.25% achieving success, while 36% were treated with a multi-dose protocol, with 83.3% responding effectively. The mean time to resolution was 28 days, with the single-dose group showing a shorter resolution time compared to the multi-dose group. Minor side effects were reported in 6% of patients, and no severe methotrexate toxicity occurred. Five patients required surgical intervention due to treatment failure or clinical deterioration.Conclusion: This study confirms that conservative management with methotrexate is a highly effective and safe treatment for ectopic pregnancy in appropriately selected patients, achieving a 90% success rate and minimizing the need for surgical intervention. Further research is needed to refine patient selection criteria and standardize treatment protocols.
Keywords: Ectopic pregnancy, Methotrexate, Conservative management, Fertility preservation